Centros municipales de recuperación de residuos sólidos valorizables en Costa Rica: situación actual y guía de buenas prácticas - Masís-Leandro, Keneth José (Instituto Tecnológico de Costa Rica, 2018)
The promotion of Material Recovery Facilities (MRF) is part of the country strategy to increase the percentage of recovered waste. However, there is a knowledge gap on the management and production processes of the MRF at the national level, which affects the good performance of the facilities. This document explores the technical and environmental factors related to the infrastructure, equipment and work procedures of municipally owned MRF in the country and proposes good practices for its design and operation. Information of 15 municipal MRF was obtained via a survey, of which 5 were visited in order to corroborate and expand the information collected. In 80% of the facilities, less than 41 ton / month of waste are processed and in 93% of them the separation operation is carried out manually on a static surface, this separation method is suitable for the quantity of waste processed in 87% of cases. The location, topography and accessibility of the lands are generally adequate and do not negatively affect the performance of the facilities. In most cases, the infrastructure was not designed to function as a MRF, so its characteristics are not oriented to maximum efficiency in the operation. The absence of records and written work procedures is a constant in the facilities studied. In most cases, inadequate ergonomic conditions were identified in the classification stations, absence of methods to evaluate the performance of the operators and deficiencies in the personnel training process. The good practices proposed to influence the identified factors were validated in a workshop with representatives of the sector.
Proyecto de Graduación (Licenciatura en Ingeniería Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Ambiental, 2018.
Keywords: Gestión; Residuos; Infraestructura; Tecnología; Procedimientos